2018
DOI: 10.1063/1.5010421
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite amplitude electroconvection in dielectric liquids

Abstract: Charge injection induced electroconvection in a dielectric liquid lying between two parallel plates is numerically simulated in three dimensions (3D) using a unified lattice Boltzmann method (LBM). Cellular flow patterns and their subcritical bifurcation phenomena of 3D electroconvection are numerically investigated for the first time. A unit conversion is also derived to connect the LBM system to the real physical system. The 3D LBM codes are validated by three carefully chosen cases and all results are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 60 publications
7
24
0
1
Order By: Relevance
“…Both the rolling pattern and square pattern have the same non-dimensional linear growth rate (~0.896 as  in Eq. (18)), which agrees with the previously reported linear stability analysis[42] and the unified SRT LBM numerical model[49] (supplementary materials for validation). After about * 5 t = from the initial perturbation, the growth rate curves for square and rolling vortices patterns diverge.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Both the rolling pattern and square pattern have the same non-dimensional linear growth rate (~0.896 as  in Eq. (18)), which agrees with the previously reported linear stability analysis[42] and the unified SRT LBM numerical model[49] (supplementary materials for validation). After about * 5 t = from the initial perturbation, the growth rate curves for square and rolling vortices patterns diverge.…”
supporting
confidence: 90%
“…6(d) verifies that the dynamic mode 0.908 r  =dominates the flow system. The growth rates of rolling and square patterns are similar to each other, which was also observed in the previous report[49]. Unstable dynamic modes visualized by z perturbation has the greatest of projection (b=1.826) on this eigenmode; therefore, it contains most of the energy of the system.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Governing equations yield four non-dimensional parameters that describe the system's state [12,[17][18][19][20][21].…”
Section: Non-dimensional Analysis and Solution For Hydrostatic Statementioning
confidence: 99%
“…Other numerical models used to study EC phenomena include the particle-in-cell method [30], finite volume method with flux-corrected transport [31], total variation diminishing scheme [5,8,[14][15][16], and the method of characteristic [4]. Recently, Luo et al showed that a unified Lattice Boltzmann model (LBM) matches the linear and finite amplitude stability criteria of the subcritical bifurcation in EC flow [18][19][20][21] for both 2D and 3D flow scenarios. This unified LBM transforms the elliptic Poisson equation to a parabolic reaction-diffusion equation and introduces artificial coefficients to control the evolution of the electric potential, which may result in ambiguity in the numerical results.…”
Section: Introductionmentioning
confidence: 99%